Proyecto De Factibilidad Para La Implementación De Una Empresa Productora Y Comercializadora De Pan En La Parroquia El Lucero, Cantón Calvas, Provincia De Loja” - Jiménez Ludeña, Sandra Cecibel (2016)
This research was conducted at the Parroquia El Lucero, Canton Calves, Province of Loja aimed at presenting a business proposal entitled "PROJECT FEASIBILITY FOR IMPLEMENTATION OF A PRODUCTION COMPANY AND DISTRIBUTOR OF BREAD IN THE PARISH LUCERO, CANTON BALD Loja province. "The same that is geared to both economic and social development of the above parish, province and country. To effect the performance of the different objectives was based on knowledge and theoretical framework to present an appropriate proposal, he also need to use some methods such as the Scientific, Inductive, Deductive and Statistical method; and investigative techniques such as Inquiry. In the market study three types of claims which are determined: the potential demand at a rate of 89.20 % that households consume bread, the actual demand of 93.47 % and 77.96 % effective demand which indicated that if they are in buy the product. With regard to the survey interview was conducted at 2 shops selling bread in the parish Lucero. With technical study found that the installed capacity will be 3,837,600 units and capacity utilization would be 390,000 units a year, was made the macro and micro localization company and the respective programs of the production process flow of the product. In the studio operating organizational legislative, executive, consultant, assistant , and established and also the functions of each job in the manual function was determined. The corporate name of the company is “MAXIPAN Co. Ltda." Within the financial study found that the initial investment is $ 23.557.57 which the equity is 70.20 % and 29.80 % foreign capital; price in each pan will be offered the first year will be $ 0.20 cents. The financial evaluation yielded the following results: Net Present Value is $ 283,943.17; Internal Rate of Return of 70.45 %; Benefit Cost Ratio is 1.96; Capital Recovery Period is 3 years, 4 months and 2 days, as the sensitivity analysis for cost increases is 43.60 % , giving a result of 0.98 % and declining revenue models with 26.50 total of 0.99% of these results indicates that the project will not be noticeable . With all these aspects mentioned above it is concluded that the implementation of the enterprise is feasible creation therefore recommended.